Since y varies directly as x, we have that this expression is true:
![y=kx](https://img.qammunity.org/2023/formulas/mathematics/college/zfnjlk9kn7jg7cyy0nlnepmsiaxj3b2oge.png)
Now, we are given the information that y=80 when x=32, then we can find k easily like this:
![\begin{gathered} y=kx \\ \Rightarrow80=k\cdot(32) \\ \Rightarrow k=(80)/(32)=(5)/(2) \\ k=(5)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cj2923hswgqr6s4as9mssrk9s63owepamy.png)
Finally, to find x when y=100, we substitute each value and solve for x the resulting expression:
![\begin{gathered} y=kx \\ \Rightarrow100=(5)/(2)\cdot x \\ \Rightarrow100\cdot2=5x \\ \Rightarrow200=5x \\ \Rightarrow x=(200)/(5)=40 \\ x=40 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j79hjesz7ixs0i25l8btci8gish6dktyt5.png)
Therefore, x=40 when y=100